2014
DOI: 10.1109/msp.2013.2296076
|View full text |Cite
|
Sign up to set email alerts
|

Score-Informed Source Separation for Musical Audio Recordings: An overview

Abstract: In recent years, source separation has been a central research topic in music signal processing, with applications in stereo-to-surround up-mixing, remixing tools for DJs or producers, instrument-wise equalizing, karaoke systems, and pre-processing in music analysis tasks. Musical sound sources, however, are often strongly correlated in time and frequency, and without additional knowledge about the sources a decomposition of a musical recording is often infeasible. To simplify this complex task, various method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 23 publications
0
55
0
3
Order By: Relevance
“…The separation performance achievable by these techniques is very limited in reverberant environments [5], [6] where the sources' STFT coefficients are quite overlapped. A more recent class of algorithms known as informed source separation [7], [8] utilizes prior information about the sources to guide the separation process, and was shown to be successful in many contexts using different types of prior information. For instance, such information may include musical scores of the corresponding music sources [7], [9], [10] or text of the corresponding speech sources [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation performance achievable by these techniques is very limited in reverberant environments [5], [6] where the sources' STFT coefficients are quite overlapped. A more recent class of algorithms known as informed source separation [7], [8] utilizes prior information about the sources to guide the separation process, and was shown to be successful in many contexts using different types of prior information. For instance, such information may include musical scores of the corresponding music sources [7], [9], [10] or text of the corresponding speech sources [8].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent class of algorithms known as informed source separation [7], [8] utilizes prior information about the sources to guide the separation process, and was shown to be successful in many contexts using different types of prior information. For instance, such information may include musical scores of the corresponding music sources [7], [9], [10] or text of the corresponding speech sources [8]. In some approaches this symbolic information is then converted to audio using a MIDI synthesizer for musical scores [9], [10] or a speech synthesizer for text [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the review presented it may be concluded that issues of retrieval and recommendation are interconnected and these two approaches when joint together may make both processes more reliable. Also, new strategies such as for example separating music tracks at the pre-processing phase [3][8] [28] [29] and extending vector of parameters by descriptors related to a given musical instrument components that are characteristic for the specific musical genre to music genre classification should be more thoroughly pursued [3][28] [29].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most promising, one finds sinusoidal modeling (SM) (Serra and Smith 1990) that was extensively exploited over the last two decades. There are also many examples of algorithms that were implemented within many research studies (Bregman 1990;Casey and Westner 2000;de Cheveigne 1993;Dziubiński et al 2005;Eweret et al 2014;Gerber et al 2012;Gillet and Richard 2008;Herrera et al 2000). Uhle et al (2003) designed a system for drum beat separation based on Independent Component Analysis.…”
Section: Music Track Separationmentioning
confidence: 99%